Experimental and Analytical Study Approach of Artificial Basilar Membrane Prototype (ABMP) - Harto Tanujaya; Hirofumi Shintaku; Dai Kitagawa; A. Adianto; S. Susilodinata; Satoyuki Kawano (Institute for Research and Community Services, Institut Teknologi Bandung, 2013)
In this research, we have developed, fabricated, tested, and analyzed an artificial basilar membrane prototype (ABMP), which works using sinusoidal waves of various frequencies. The design of the prototype has a trapezoidal shape with a length of 30 mm and a width of 2 to 4 mm. The research was carried out experimentally and analytically. Experimentally, the ABMP's vibration was measured using a laser Doppler vibrometer (LDV) and a function generator to generate various frequencies. The analytical approach is discussed based on the Wentzel Kramer Brillouin method (WKB). The results show that resonance frequencies can be reached within the range of human hearing, between 20 Hz to 20 kHz.